PENGEMBANGAN SIMIPA BERBASIS ANDROID MENGGUNAKAN METODE SCRUM PADA MODUL MAHASISWA - Ardiansyah Ardiansyah; Kelvin Putra; Dwi Sakethi; Anie Rose Irawati (Jurnal Pepadun, 2021)
Academic activities are a learning process that is carried out based on the curriculum in university to produce quality graduate students. Good academic activities can be supported by having a system that helps academic activities at a university. FMIPA University of Lampung currently has a web-based MIPA information system (SIMIPA) which is used as a system that can support the administrative service process for FMIPA University Lampung students. Information technology that is currently developing rapidly shows that there is a need for development to be done on the SIMIPA as an effort to increase the benefits of SIMIPA. Development of an android-based student module SIMIPA application is one of the systems developed to improve services for FMIPA students at the University of Lampung. This application development will use the Scrum method. The scrum method is a software development framework from implementing Agile Development method for software projects. Development of this application is based on the product backlog which is divided into 8 sprints. The result of this research is the successful development of the SIMIPA application module for academic students using Scrum method. This is evidenced by testing using black box testing which shows the overall functional needs of the student module SIMIPA application as expected.